2017
DOI: 10.1049/iet-nbt.2017.0023
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesised silver and copper nanoformulation as foliar spray to control bird's eye spot disease in tea plantations

Abstract: Tea leaves have economic importance in preparation of the popular beverage of the world "tea". Bird's eye spot disease of tea leaves creates significant revenue loss in tea trade of many tea plant cultivating countries. Management of this disease by silver (AgNps) and copper (CuNps) nanoparticles that are biosynthesised by efficient antagonists was studied. The biocontrol agents like Pseudomonas fluorescens, Trichoderma atroviride and Streptomyces sannanensis were evaluated for nanoparticle synthesis against C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…69.90% was the highest percentage inhibition found against Poria on the 15th day of incubation by silver NPs at 5 ppm concentration in comparision with Carbendazim which showed 90.12% inhibiton of Poria at the same stage ( Table 2). The percentage inhibition of P. theae isolates which was high at initial stage for Ag Nps synthesized culture filtrate was in the range from 59.42 to 79.76%, followed by Cu NPs (43.66 -76.19%) [14]. Against Phomopsis, 67.47% was the highest percentage inhibition found by silver NPs on the 15th day at 5 ppm (Table 3), as compared with the green synthesized silver nanoparticles which were found highly toxic against pathogenic bacteria and fungi at a concentration of 30 ppm [24].…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…69.90% was the highest percentage inhibition found against Poria on the 15th day of incubation by silver NPs at 5 ppm concentration in comparision with Carbendazim which showed 90.12% inhibiton of Poria at the same stage ( Table 2). The percentage inhibition of P. theae isolates which was high at initial stage for Ag Nps synthesized culture filtrate was in the range from 59.42 to 79.76%, followed by Cu NPs (43.66 -76.19%) [14]. Against Phomopsis, 67.47% was the highest percentage inhibition found by silver NPs on the 15th day at 5 ppm (Table 3), as compared with the green synthesized silver nanoparticles which were found highly toxic against pathogenic bacteria and fungi at a concentration of 30 ppm [24].…”
Section: Resultsmentioning
confidence: 95%
“…The average size was determined to be around 50 nm in size, similar to the analysis in which the biosynthesised Ag NPs and Cu Nps were determined using PS analyser. The curve reveals that Ag NPs were polydispersed in natue, with average size ∼250 nm [14].…”
Section: Particle Size Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…According to the study of Gnanamangai et al [9], it was found that the application of 1.5 ppm (1.5 mg/L) Bionanocper had the greatest effect on the yield of tea. At the same time, Mamyandi et al [10] chose the concentration of 1, 2, and 3 mg/L to study the foliar spraying of nano-iron.…”
Section: Treatment Groupsmentioning
confidence: 99%
“…However, [8] recently reported that green synthesis of AgNPs using plant extracts produces NPs that have different morphological characteristics, including sizes, stability, and electronegativity, which contribute to their bacteriostatic and fungistatic inhibitory potentials at significantly low concentrations. Black tea extract used in the current study for the synthesis of AgNPs is a brain stimulating beverage that is extracted from the leaves of the tea plant (Camellia sinensis), which is widely cultivated in several Asian countries [9].…”
Section: Introductionmentioning
confidence: 99%